Arrhythmogenic Right Ventricular Cardiomyopathy: Considerations from in Silico Experiments - Wilders, Ronald (Frontiers in Physiology, 2012)
Objective: Arrhythmogenic right ventricular cardiomyopathy (ARVC) is associated with remodelling of gap junctions and also, although less well-defined, down-regulation of the fast sodium current. The gap junction remodelling and down-regulation of sodium current have been proposed as contributors to arrhythmo¬genesis in ARVC by slowing conduction. The objective of the present study was to assess the amount of conduction slowing due to the observed gap junction remodelling and down-regulation of sodium current. Methods: The effects of (changes in) gap junctional conductance, cell dimensions and sodium current on both longitudinal and transversal con¬duction velocity were tested by simulating action potential propagation in linear strands of human ventricular cells that were either arranged end-to-end or side-by-side. Results: A 50% reduction in gap junction content, as commonly observed in ARVC, gives rise to an 11% decrease in longitudinal conduction velocity and a 29% decrease in transverse conduction velocity. A down-regulation of the sodium current through a 50% decrease in peak current density as well as a −15 mV shift in steady-state inactivation, as observed in an experimental model of ARVC, decreases conduction velocity in either direction by 32%. In combination, the gap junction remodelling and down-regulation of sodium current result in a 40% decrease in longitudinal conduction velocity and a 52% decrease in transverse conduction velocity. Conclusions: The gap junction remodelling and down-regulation of sodium current do result in conduction slowing, but heterogeneity of gap junction remodelling, in combination with down-regulation of sodium current, rather than gap junction remodelling per se may be a critical factor in arrhythmogenesis in ARVC.